Low-Abundance Drug-Resistant HIV-1 Variants in Antiretroviral Drug-Naive Individuals: A Systematic Review of Detection Methods, Prevalence, and Clinical Impact. (6th December 2019) - Mbunkah, Herbert A; Bertagnolio, Silvia; Hamers, Raph L; Hunt, Gillian; Inzaule, Seth; Rinke De Wit, Tobias F; Paredes, Roger; Parkin, Neil T; Jordan, Michael R; Metzner, Karin J
Abstract: Background: The presence of high-abundance drug-resistant HIV-1 jeopardizes success of antiretroviral therapy (ART). Despite numerous investigations, the clinical impact of low-abundance drug-resistant HIV-1 variants (LA-DRVs) at levels <15%–25% of the virus population in antiretroviral (ARV) drug-naive individuals remains controversial. Methods: We systematically reviewed 103 studies assessing prevalence, detection methods, technical and clinical detection cutoffs, and clinical significance of LA-DRVs in antiretroviral drug-naive adults. Results: In total, 14 919 ARV drug-naive individuals were included. Prevalence of LA-DRVs (ie, proportion of individuals harboring LA-DRVs) was 0%–100%. Technical detection cutoffs showed a 4 log range (0.001%–10%); 42/103 (40.8%) studies investigating the impact of LA-DRVs on ART; 25 studies included only individuals on first-line nonnucleoside reverse transcriptase inhibitor-based ART regimens. Eleven of those 25 studies (44.0%) reported a significantly association between preexisting LA-DRVs and risk of virological failure whereas 14/25 (56.0%) did not. Conclusions: Comparability of the 103 studies is hampered by high heterogeneity of the studies' designs and use of different methods to detect LA-DRVs. Thus, evaluating clinical impact of LA-DRVs on first-line ART remains challenging. We, the WHO HIVResNet working group, defined central areas of future investigations to guide further efforts to implement ultrasensitive resistance testing in routine settings. Abstract : We systematically assessed 103 studies on the prevalence of low-abundance drug-resistant HIV-1 variants and their impact on antiretroviral therapy, which remains uncertain. Important topics were defined to guide further efforts to implement ultrasensitive resistance testing in routine settings.